Belief functions: theory and applications : Third International Conference, BELIEF 2014, Oxford, UK, September 26-28, 2014. Proceedings - Cuzzolin, Fabio (Lecture Notes in Computer Science, 2014)
This book constitutes the thoroughly refereed proceedings of the Third International Conference on Belief Functions, BELIEF 2014, held in Oxford, UK, in September 2014. The 47 revised full papers presented in this book were carefully selected and reviewed from 56 submissions. The papers are organized in topical sections on belief combination; machine learning; applications; theory; networks; information fusion; data association; and geometry.